Die historischen Spiegelschwankungen des Kaspischen Meeres und Probleme ihrer Deutung - Ehlers, Eckart (ERDKUNDE, 1971)
Based on the evaluation of old travel accounts and observations, particularly on the Caucasian coast of the Caspian, changes of level of over 10 metres in size since Medieval times have been claimed by some researchers. Observations in North Iran and the results of geological investigations on the Soviet Caspian coast lead to the following conclusions: 1) the Caspian Sea has not exceeded the 22 metre level in historical times, but has attained it at least three and perhaps even four times. Its lowest level was at -32 metres NN. 2) the causes of the fluctuations in the level of the Caspian Sea are climatic, above all, thermal changes on the surface of the sea. The differing flow yields of the rivers is also subordinate to this basic principle of the Caspian water balance and the appropriately resulting climatic changes. 3) tectonic activity has played only a sub ordinate role in the evalution of historical changes in level. Reports of above average sea levels on the Caspian west coast form exceptions to the rule. They rise at the expense of the tectonically unstable Apsheron Peninsula, which thus assumes a special position in the context of the over 7 500 km long Caspian coast. Thus the Caspian Sea, in its historical development and the constant change from transgression phases, is revealed as a mirror of the climatic history of the Holocene. The Baku area, considered till now as representative can, as a result of recent tectonic action, be regarded as a special case. The historical changes in level, which have been observed and described in this area can thus not be regarded as characteristic for the entire Caspian Sea.